Professional Mobility as the Realization Factor of Teacher's Innovative Activity - S. A. Morozova; E. E. Symanyuk (Russian State Vocational Pedagogical University, 2015)
The article deals with the teachers' professional mobility as a factor of their readiness for innovative activity. Based on the analysis of psychological and pe- dagogic literature, the essence and structure of the given phenomenon are defined. The subject of the experimental research compiles the key qualities of profes- sional mobility and their development techniques for vocational training teachers. The aim of the study includes the identification of the key characteristics of the qualities in question. The main methodological idea is defined as follows: the professional mobility formation is the basis of teachers' productive innovative activity. The research findings made it possible to identify the components of profes- sional mobility: innovative attitude, creativity, intellectual mobility, extra-normative ac- tivity and communication skills. The research results provide the basis for effective technologies selection for developing teachers' professional mobility.